2006
DOI: 10.1111/j.1365-2613.2006.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure alters matrix metalloproteinase gene expression and activity in rat skeletal muscle

Abstract: Heart failure is associated with a skeletal muscle myopathy with cellular and extracellular alterations. The hypothesis of this investigation is that extracellular changes may be associated with enhanced mRNA expression and activity of matrix metalloproteinases (MMP). We examined MMP mRNA expression and MMP activity in Soleus (SOL), extensor digitorum longus (EDL), and diaphragm (DIA) muscles of young Wistar rat with monocrotaline-induced heart failure. Rats injected with saline served as age-matched controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 46 publications
4
28
1
Order By: Relevance
“…MMP-2 and MMP-9 are strongly up-regulated in experimental ischemia/reperfusion injury leading to degradation of basal lamina in skeletal muscle (13). Furthermore, increased expression of MMPs has also been reported in atrophying skeletal muscle after nerve injury (14), heart failure (15,16), and in the pathogenesis of inflammatory myopathies (17)(18)(19).…”
mentioning
confidence: 99%
“…MMP-2 and MMP-9 are strongly up-regulated in experimental ischemia/reperfusion injury leading to degradation of basal lamina in skeletal muscle (13). Furthermore, increased expression of MMPs has also been reported in atrophying skeletal muscle after nerve injury (14), heart failure (15,16), and in the pathogenesis of inflammatory myopathies (17)(18)(19).…”
mentioning
confidence: 99%
“…Intrinsic skeletal muscle abnormalities have been described in heart failure patients and hypothesized to play a role in exercise intolerance [1,2,3,4,5,6,7]. Skeletal muscle alterations such as atrophy, fibrosis, decreased oxidative capacity, altered myosin distribution, and contractile dysfunction have been well characterized in several experimental and clinical heart failure studies [3,6,7,8,9,10,11]. However, the causal or contributing factors responsible for muscle alterations have not been completely defined.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle evaluation was performed on rat soleus muscle as previous studies have shown that this muscle exhibits morphological and molecular alterations during short- [38] and long-term [22,34,39] heart failure. In fact, we observed that AAS group soleus muscle presented atrophy and increased collagen fractional area in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The area of soleus muscle occupied by collagen was significantly larger in the AAS than the Control group. In heart failure, skeletal muscle atrophy is accompanied by alterations in the extracellular matrix adjacent to muscle fibers and mainly involve interstitial cells apoptosis [54][55][56], and increased collagen content [57] and metalloproteinases activity [38,58]. The GH treatment attenuated muscular fibrosis as AAS-GH group presented collagen fractional area values between those in the Control and AAS groups.…”
Section: Control (N = 7)mentioning
confidence: 98%